Pembinaan Manajemen SDM untuk Optimalisasi Aktifitas Organisasi Desa - Asa Sheila Amelia (Program Studi Ekonomi Pembangunan, 2026)
This community service program aims to improve the quality of village organizational activity management through strengthening the human resource management (HRM) capacity of village officials and organizational managers. The program was implemented in Panembahan Village, Kraton District, Yogyakarta City, targeting village officials, neighborhood association (RT/RW) administrators, and representatives of youth organizations. The implementation methods included needs assessment, HRM training, focus group discussions, and mentoring on the application of organizational work tools. Program evaluation was conducted using pre-tests and post-tests to measure participants’ competency improvement, participatory observation, and participant satisfaction questionnaires. Of the 30 invited participants, 26 attended the program (86.7%). The evaluation results indicated an overall increase in participants’ competencies, with an average improvement of 36%, and the highest increase was observed in activity planning skills at 42%. In addition, the program produced 12 village organizational administrative documents, including organizational structures, job descriptions, activity report formats, work agendas, and draft standard operating procedures for public services. Participant satisfaction was categorized as high, with an average score of 4.32 on a 1–5 Likert scale. These findings demonstrate that HRM development accompanied by practice-based mentoring contributes to initial improvements in planning, coordination, and administrative management of village organizations, although sustained impacts still require continuous mentoring.